ANALYSIS OF MATHEMATICAL MODELS OF UNDERGROUND HEAT EXCHANGE DEVICES - Khamrayev, Sardor; Ibragimov , Umidjon (Innovatsion texnologiyalar, 2024)
Geothermal energy sources are widely used as a renewable energy source in building heating and cooling systems. The thermal characteristics of underground heat exchange devices are crucial for the efficient operation of geothermal heat pumps (GHPs). This article presents an analysis of recent developments in three types of GHPs widely used in large-scale systems: vertical borehole GHPs, pile-based GHPs, and horizontal borehole GHPs. Additionally, analyses of analytical and numerical models proposed for investigating heat transfer processes, taking into account various geological conditions, are presented.